Human Cytomegalovirus is Present in Alveolar Soft Part Sarcoma. Issue 9 (October 2017) - Price, Richard L.; Harkins, Lualhati; Chiocca, Ennio A.; Zhang, Paul J.; Kurt, Habibe; Iwenofu, Obiajulu H.
Abstract : Alveolar soft part sarcoma (ASPS) is an exquisitely rare sarcoma of unknown histogenesis, with a predilection for adolescents and young adults, characterized by slow progressive clinical course and high frequency of metastases. They are traditionally chemoresistant with very limited treatment options in the metastatic setting. Human cytomegalovirus (HCMV) is a DNA β-herpes virus and it is characterized by persistent lifelong and latent infection. There is growing evidence to indicate the presence of HCMV proteins and nucleic acids in glioblastoma, medulloblastoma, rhabdomyosarcoma, and a variety of solid organ malignancies of the breast, prostate, lung, and colon at very high prevalence. Immunotherapy-based clinical trials targeting specific cytomegalovirus proteins are currently in progress in the treatment of glioblastoma. Herein, we evaluated for the presence of HCMV proteins (IE1 and pp65), genes (US28 and UL96), and RNA in a cohort of ASPS. Six confirmed cases of ASPS were retrieved and full thickness sections of formalin-fixed paraffin-embedded material were stained for anti-HMCV-IE1 and anti-HCMV-pp65. Any nuclear and/or cytoplasmic staining was considered positive. DNA was purified from 50 µm of formalin-fixed paraffin-embedded material. One hundred nanogram of DNA was amplified using polymerase chain reaction for primers specific to HCMV-US28 (forward: AGCGTGCCGTGTACGTTAC and reverse: ATAAAGACAAGCACGACC) and HCMV-UL96 (forward: ACAGCTCTTAAAGGACGTGATGCG and reverse: ACCGTGTCCTTCAGCTCGGTTAAA) using Promega Taq polymerase. HCMV in situ hybridization was performed. All 6 cases of ASPS were positive for both HCMV-IE1 and HCMV-pp65. Usable DNA was available in 4 of the 6 cases. HCMV-US28 gene was found in 75% (3/4) of cases and HCMV-UL96 gene was detected in 50% (2/4) of cases. Importantly, all cases tested positive for at least 1 gene. HCMV-encoded RNA was identified in 80% (4/5) of cases. The presence of HCMV DNA, RNA along with HCMV protein indicates that HCMV is present in ASPS and may contribute to its pathogenesis.